Reconstruction of a Complex Foot Defect with a Chimeric Triple-Component Osteocutaneous SCIP–SIEA Free Flap: A Case Report and Literature Review - Berkane, Yanis; Lupon, Elise; Muret, Pierre; Laloze, Jérôme; Bertheuil, Nicolas; Herlin, Christian; Girard, Paul; Paoli, Hadrien (Archives of Plastic Surgery, 2025)
Complex defects resulting from infected bone or joints with or without osteosynthesis or prosthetic material lead to significant challenges that need to be addressed through orthoplastic approaches. Foot and ankle reconstruction is particularly difficult due to the lack of local or regional flap solutions in this highly mobile joint, which often necessitates microsurgical flaps in extended defects. In addition, rigorous bone reconstruction is critical to acute bone infection to minimize the risks of functional impairments. We present a novel approach using a chimeric osteocutaneous flap to address a complex calcaneus fracture with extended postoperative skin necrosis and septic pseudoarthrosis. A dual skin paddle (16 × 6.5 cm and 14 × 4.5 cm) was created using a superficial inferior epigastric artery (SIEA)-to-superficial circumflex iliac artery (SCIA) anastomosis, while the 7-cm pedicle was increased using a deep inferior epigastric artery graft, which was anastomosed to the tibial anterior vessels. The vascularized iliac crest component enabled optimal reconstruction of the bone defect with rapid healing, while the combined SCIP (superficial circumflex iliac artery perforator)–SIEA skin flap was used to cover the bone reconstruction and skin defect. This microsurgical reconstruction allowed optimal functional recovery at 12 months with successful bone integration and soft tissue coverage. The step-by-step intraoperative technique is described through Video 1 and Supplementary Video 2.
Keywords: foot reconstruction; SCIP flap; chimeric flap; ankle reconstruction; SIEA flap